Peer Assessment of Skimming and Scanning to Improve Reading Comprehension - Perlaza Estupiñán, Jimmy Javier (2020)
This research implemented peer-assessment, skimming, and scanning to improve reading comprehension. The research was applied at a public high school in Guayaquil. The sample was 25 students of second baccalaureate with a majority of them being at an A1 level with some students in an A2 English level. This action research was supported by qualitative and quantitative instruments. Skimming and scanning strategies were scaffolded, monitored and developed during the implementation with different activities. Results show that the impact of the innovation was Cohen d= 3.29 which indicates a large impact in learning. After applying the innovation, 76% of the students showed an improvement in their reading comprehension as evidenced in a pre and post-test. This result was supported by the changes in attitude that were observed during the process of the activities as well. This innovation demonstrated that by applying peer-assessment of skimming and scanning strategies learners can improve their reading comprehension in a second language.